A Comparative Study of Cool Roof and Green Roof Performance in Tropical Area of Indonesia - Budhiyanto, Aris; Tampubolon, Angela Christysonia (Journal of Architectural Research and Design Studies, 2025)
This study examines the performance of cool roofs and green roofs in a tropical climate in Indonesia. It compares a modified pitched roof designed as a cool roof with a flat roof equipped with vegetation functioning as a green roof on single storey building. A simulation method using EnergyPlus is employed to model the building and evaluate roof performance. The evaluation focuses on their efficacy in mitigating heat flux, enhancing thermal comfort, and reducing energy consumption. The results indicate that green roofs can decrease heat flux by up to 91%, lower temperature by up to 13.14°C, and reduce energy consumption by approximately 60%. Meanwhile, cool roofs can achieve up to a 95% reduction in heat flux, a temperature decrease of up to 11.58°C, and an energy savings of up to 55%. Specifically, green roofs demonstrate superior performance in reducing heat gain within the room during daytime. Conversely, cool roofs are more effective in providing thermal comfort during nighttime. For buildings predominantly occupied during the day, the application of green roofs is likely to result in greater energy savings compared to cool roofs. Keywords: Cool Roof; Green Roof; Performance Comparison; Tropical Area